Competitive Roles of DNRA and Denitrification on Organic Nitrogen Dynamics in Partially Saturated Soil‐Water Systems - Liu, Lecheng; Zheng, Tianyuan; Qiu, Yingying; Hao, Yujie; Ma, Haoran; Zheng, Xilai; Guadagnini, Alberto (Water resources research, 2025)
We focus on the competition between nitrate/nitrite ammonification (also termed dissimilatory nitrate reduction to ammonium (DNRA)) and denitrification processes taking place across partially saturated water‐soil systems. The study is motivated by the observation that the joint presence of dissolved organic nitrogen (DON) and redox fluctuation in the vadose zone poses potential risks for generation of nitrates (NO3−‐N) that can then be reduced to ammonium (NH4+‐N) through DNRA. We examine nitrogen dynamics induced in natural soil samples subject to controlled drying‐wetting cycles. Upon experimental evidences, we estimate the parameters driving the kinetics associated with nitrogen transformation. This enables us to document a competition between DNRA and denitrification during wetting periods. We find that the increasing the carbon‐to‐nitrogen (C/N) ratio in the system yields a significant increase of DNRA rates, with a corresponding increase of their contribution to nitrate reduction. The rate of DNRA is documented to be (a) significantly faster in loam than in sandy loam, due to dissolved carbon release from loam aggregates, and (b) more effective in the presence of amino acid than urea in the natural soil, due to the role of amino acid as carbon source. Our analysis further suggests the relevance of hydrogeochemical factors (e.g., moisture variation, soil texture, and C/N ratio) on DON transformation through the influence of functional microorganisms. These insights advance our understanding of nitrogen dynamics in agroecosystems, which has significant implications for environmental management practices aimed at controlling NO3−‐N pollution in partially saturated soils. Key Points Competition between denitrification and dissimilatory nitrate reduction to ammonium (DNRA) is identified in transformation of organic nitrogen Contribution of DNRA to nitrate reduction depends on soil texture, C/N ratio and nitrogen speciation Ignoring the occurrence of DNRA may underestimate nitrate leaching through vadose zone